A Constituição Imperial de 1824: Uma breve análise dos aspectos sociais, políticos, econômicos jurídicos - Rossana Teresa Curioni Mergulhão; Bazilio de Alvarenga Coutinho Junior; Elton Fernando Rossini Machado (Araucaria)
Inevitable say that the Brazilian Constitution of 1988 refl ects an existing reality in our nation. Also notorious that its origin brought a not too distantpast, inserted into your body experiences that have brought benefi ts to society are still there. The constitutional development was necessary for Brazil to move forward, and from this perspective, we will study important aspects of theImperial Constitution of 1824, the fi rst constitution in our country soon after the cessation of colonial Brazil, and who translated the strong features of the European elite, where slavery was still existing. The centralization of power at that time answers many questions about the Constitution currently in force, which reveals more freedom with regard to fundamental rights of citizens, existing in its minimum degree in another letter undemocratic. Analysis, therefore, these two moments.